Construct a phonetic database and develop a phonetic transcription in Gujarati language - Tank, V.P; Manavadaria, M.S (International Journal of Computer Sciences and Engineering, 2025)
Last few decades are witness of development of phonetic transcription as a part of linguistic research in various languages like American English, Spanish, and Japanese etc. Few amount of work has been done for Indian languages by researchers. So this paper particular focuses in Gujarati Language which is official regional Indian language. This research paper mainly contains two important parts as far as linguistic research is concern first one is creation of phonetic database and second is to develop a phonetic transcription in Guajarati language. For better analysis for bilingual and multilingual analysis phonetic transcription of Gujarati language has been compared with American English.